2014
DOI: 10.1007/s11325-014-1003-z
|View full text |Cite
|
Sign up to set email alerts
|

Evening and morning exhaled volatile compound patterns are different in obstructive sleep apnoea assessed with electronic nose

Abstract: Evening and morning exhaled volatile compound patterns are different in OSA. This might affect the ability of electronic noses to identify this disorder. Overnight alterations in volatile substances need to be taken into account during exhaled breath measurements in OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 31 publications
4
42
0
Order By: Relevance
“…Overall, lack of correction of BP with tumor size and site, as well as comorbidities, likely account for uncertainty in the interpretation of results because the amount of exhaled compounds may be significantly influenced by these variables. [81][82][83][84][85][86][87][88]. As expected, the performance is dependent on the disease taken into account, with the best performance observed in discriminating patients with OSA syndrome from obese , as e-nose discriminative ability is effectively able to target metabolic changes after continuous-positive airway pressure ventilation only in patients without comorbidities [84].…”
Section: Indirect Interpretationmentioning
confidence: 54%
“…Overall, lack of correction of BP with tumor size and site, as well as comorbidities, likely account for uncertainty in the interpretation of results because the amount of exhaled compounds may be significantly influenced by these variables. [81][82][83][84][85][86][87][88]. As expected, the performance is dependent on the disease taken into account, with the best performance observed in discriminating patients with OSA syndrome from obese , as e-nose discriminative ability is effectively able to target metabolic changes after continuous-positive airway pressure ventilation only in patients without comorbidities [84].…”
Section: Indirect Interpretationmentioning
confidence: 54%
“…Interestingly, this difference was present only at morning and not before sleep which was supported by the fact that the evening and morning breathprints were different in OSA [9]. A significant relationship was found between volatile compound mixtures and AHI, in one [79], but not in the other study [9]. CPAP therapy significantly altered exhaled breathprints [79], however other studies have shown that these alterations are different if OSA is accompanied with comorbidities such as diabetes mellitus, metabolic syndrome and chronic heart failure [99].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 88%
“…Moreover, breath can be collected before and after sleep to study sleep-related changes; pertinent in OSA [9][10][11][12][13][14]. Moreover, Amann et al developed a sampling system to analyse exhaled volatile organic compounds (VOCs) even during sleep [15,16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Polysomnography was performed as described previously [9] using Somnoscreen Plus Tele PSG (Somnomedics GmbH, Germany) according to the guidelines [19]. Apnoea-hypopnoea index (AHI), respiratory disturbance index (RDI) and oxygen desaturation index (ODI) were recorded and used as indices for OSA severity.…”
Section: Polysomnographymentioning
confidence: 99%
“…Theoretically, lung function may vary due to two main reasons. On one hand, overnight changes in airway broncho-reactive mediator concentrations were reported and may influence operational lung volumes [8][9][10][11][12]. On the other hand, OSA is associated with increased sympathetic and decreased parasympathetic tone during sleep, especially during apnoeic periods [13][14][15], which may result in alterations in resting bronchial tone [16][17][18].…”
Section: Introductionmentioning
confidence: 99%